The Effect of Adversity Intelligence Towards Social Adjustments in Identic Drug Users (A Study on Metadon Housing Therapy Program’s Participants (Ptrm) (International Journal of Psychosocial Rehabilitation, 2020)
In eventually get through methadone needed the ability to adapt to the social environment, in addition MMT patients are required to be able to be acclimated with the for follow therapy. One of the factors that forms the ability adjustment society is adversity intelligence. The purpose of this research is to know the influence of adversity intelligence on social adjustment on drug users injection who joined the methadone maintenance treatment (MMT). The research is the causal-comparative study using purposive sampling technique obtained a number of patients samples 120 MMT consisting of 60 MMT Tambora Community Health Center and 60 MMT Grogol Petamburan Community Health Center. Adversity intelligence is measured using a Stoltz ARP scale (2000) with a reliability (α ) =   0.91 and a scale of social adjustment (1960) with a reliability (α) = 0.901 of 19 valid items. Based on the one way test ANOVA value obtained sig (p) = 0.945;   (p) = 0.945> 0.05) , which means hypothesis rejected. Known also the subject of that age and experience drop out subject influence on social adjustment. A subject with adulthood the beginning and subject able to follow therapy (not drop out) more having social adjustment good. Besides ever therapy will not affect social skills adjustment.